Reasons Underlying the Extraction of Permanent Teeth in Patients Attending A.B.S.M.I.D.S - Yadav, Anirudh; Karikal, Aravind (Journal of Health and Allied Sciences NU, 2016)
Extraction of permanent teeth is very common surgical procedure for all oral and maxillofacial surgeons. The study was undertaken to know the reason for teeth extraction and its association with age, gender and type of teeth removed. A prospective cross sectional survey was carried out in patients attending the Department of Oral and Maxillofacial Surgery in A.B.S.M.I.D.S between July 2015 and August 2015. The data was collected and computer software SPSS 19 was used for statistical analysis. In this study a total of 372 extractions in 248 patients was included. The reasons for extraction were classified into caries, periodontal disease, orthodontic reasons, prosthodontic, trauma and others (patient request). Dental caries still remains the most common reason for teeth extraction followed by periodontal reasons. More number of teeth extractions is seen in the female patients as compared to the male.
Keywords: teeth extraction; dental caries; periodontal disease